Impact of dietary antioxidants on sport performance: A review - Braakhuis, A. J.; Hopkins, W. G. (Sports Medicine, 2015)
Many athletes supplement with antioxidants in the belief this will reduce muscle damage, immune dysfunction and fatigue, and will thus improve performance, while some evidence suggests it impairs training adaptations. Here we review the effect of a range of dietary antioxidants and their effects on sport performance, including vitamin E, quercetin, resveratrol, beetroot juice, other food-derived polyphenols, spirulina and N-acetylcysteine (NAC). Older studies suggest vitamin E improves performance at altitude, with possible harmful effects on sea-level performance. Acute intake of vitamin E is worthy of further consideration, if plasma levels can be elevated sufficiently. Quercetin has a small beneficial effect for exercise of longer duration (>100 min), but it is unclear whether this benefits athletes. Resveratrol benefits trained rodents; more research is needed in athletes. Meta-analysis of beetroot juice studies has revealed that the nitrate component of beetroot juice had a substantial but unclear effect on performance when averaged across athletes, non-athletes and modes of exercise (single dose 1.4 ± 2.0 %, double dose 0.5 ± 1.9 %). The effect of addition of polyphenols and other components to beetroot juice was trivial but unclear (single dose 0.4 ± 3.2 %, double dose -0.5 ± 3.3 %). Other food-derived polyphenols indicate a range of performance outcomes from a large improvement to moderate impairment. Limited evidence suggests spirulina enhances endurance performance. Intravenous NAC improved endurance cycling performance and reduced muscle fatigue. On the basis of vitamin E and NAC studies, acute intake of antioxidants is likely to be beneficial. However, chronic intakes of most antioxidants have a harmful effect on performance.